Experimental Analysis of Major and Minor Flow Losses in Centrifugal Pump Piping Systems - Syakri Syakri; Burhan Hafid; Abdul Gafur (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Pumping and piping systems play a crucial role in transporting fluids in industrial and laboratory applications. However, energy losses occurring within the piping network can significantly reduce hydraulic performance and overall system efficiency. This study aims to experimentally analyze major and minor head losses in a centrifugal pump piping system under controlled laboratory conditions. The experimental setup employed a ½-inch PVC pipe with three piping configurations, namely a straight pipe, a 45° elbow, and a 90° elbow. Flow conditions were varied by adjusting the valve opening to produce different discharge rates. The measured parameters included flow rate and pressure difference, while flow velocity, Reynolds number, major head loss, and minor head loss were determined through standard fluid mechanics calculations. The experimental results indicate that increasing the flow rate leads to a significant increase in total head loss due to higher flow velocity and greater friction along the pipe wall. Furthermore, the 90° elbow generated higher minor head loss than the 45° elbow because the sharper change in flow direction produced stronger turbulence. These findings are consistent with fluid flow theory and demonstrate that both flow rate and fitting geometry have a substantial influence on energy losses. The results can serve as a useful reference for designing and operating more efficient centrifugal pump piping systems.